(untitled) (Al-Qamar, 2023)
Allah, the Exalted and Exalted, bestowed upon His chosen servants the position of Prophethood and Messenger ship, and also characterized them with high moral and distinguished qualities and perfections. These attributes and perfections are the characteristics of the Prophets, peace be upon them, which distinguish them from other human beings. The Holy Prophet (PBUH) is the Imam and the Seal of the most distinguished group of Prophets. You (PBUH) have collected the praises and virtues, miracles and perfections, and characteristics and distinctions of all prophets and messengers in the essence of teaching. There is no equal to you in this feature. In this paper, a brief introduction of the Urdu books written on the characteristics of the Prophet (PBUH) has been presented. Also, the important topics of these books have been discussed.